Forgotten Saint-Simonian travelers in Egypt : Suzanne Voilquin, Ismayl Urbain, and Jehan d'Ivray - Ragan, John David (The American University in Cairo Press, 2025)
"This book tells the stories of two French women and a French African man, travelers connected to the Saint-Simonian utopian socialists, who came to work for the Egyptian government in the 1830s. They have been marginalized and excluded from the historical record, because they were women, not part of the colonial elite, or of mixed racial heritage. This history brings them alive through extensive archival research and vibrant storytelling. There is Suzanne Voilquin, a practicing midwife in Cairo who was involved in left-wing popular politics in Paris and became the editor of one of the first feminist newspapers ever published (1832-34). The second traveler, Thomas Ismayl Urbain, was born in French Guyana, where his mother was born a slave and his father was a French sea captain. "Jehan d'Ivray" is the pen name of the third traveler, a teenage woman who married an Egyptian studying medicine in France, and traveled with him to Egypt in 1879. She wrote more than twenty books, including a retrospective look at Suzanne Voilquin and women in the Saint-Simonian movement, bringing the story full circle to another generation. Their stories brilliantly illustrate the paradoxes of nineteenth century colonialism in Egypt. Suzanne Voilquin grew up in the Parisian working class and sympathized deeply with Egyptians but initially exoticized the differences between Egypt and her home country, while Urbain, a literary pioneer in black pride, nevertheless joined the French army and saw his role in the colonial occupation as a means of helping indigenous people. These characters transcend the neat binary of East and West and offer a rich, nuanced window onto the experiences of French travelers in Egypt during the nineteenth century"--